Avaliação ecotoxicológica de efluentes industriais utilizando Danio rerio Hamilton-Buchanan, 1822 (TELEOSTEI, CYPRINIDAE) - Castro, Ana Anita Alexsandra Seixas de (2008)
The industrial effluents are one of the main sources of water pollution. For an appropriate characterization and control of their discharges, the most efficient strategy is the integrated use of chemical, physical and ecotoxicological analyses. The aims of this study were to asses the efficiency of the treatment plant of a textile industry performing acute toxicity tests and physical-chemical analyses of the effluents before and after the treatment, besides evaluate the toxicity of the effluents of the Treatment System of Liquids Effluents (Sistema de Tratamento de Efluentes Líquidos - SITEL) of Distrito Industrial de Natal (DIN) and some of their physical-chemical variables. The species used in the ecotoxicological tests was the fish Danio rerio. The results showed that the treatment plant reduced significantly (around 50%) the toxicity of the raw textile effluent in only three of the seven tests but, in general, it promoted the reduction of the physical-chemical parameters analyzed. The toxicity and the physical-chemical factors of the effluents of SITEL of DIN varied among the tests and show the importance of monitoring their discharges in the Potengi river, one of the most important rivers of the Rio Grande do Norte state